2008
DOI: 10.1186/gb-2008-9-2-r44
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome functional analysis identifies novel components required for mitotic spindle integrity in human cells

Abstract: A loss-of-function screen for siRNAs that arrest human cells in metaphase reveals genes involved in mitotic spindle integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 33 publications
2
53
0
Order By: Relevance
“…Genome-wide siRNA libraries were screened for regulation of TNF-induced IL-8 scretion in HeLa cells (33)(34)(35), and several siRNAs targeting BMX were found to be potent inhibitors (data not shown). A selection of siRNAs designed to target different sequences in the human BMX mRNA were transfected in HeLa cells according to the HiPerfect protocol, and TNF-induced IL-8 was measured (Fig.…”
Section: Depletion Of Bmx Protein Results In Decreased Secretion Of Il-8mentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide siRNA libraries were screened for regulation of TNF-induced IL-8 scretion in HeLa cells (33)(34)(35), and several siRNAs targeting BMX were found to be potent inhibitors (data not shown). A selection of siRNAs designed to target different sequences in the human BMX mRNA were transfected in HeLa cells according to the HiPerfect protocol, and TNF-induced IL-8 was measured (Fig.…”
Section: Depletion Of Bmx Protein Results In Decreased Secretion Of Il-8mentioning
confidence: 99%
“…All small interfering RNAs (siRNAs) were synthesized at Novartis with the target sequences listed in Supplemental Table 2. The siRNA libraries have been described earlier and comprise siRNA targeting 24,373 predicted human genes (33), as well as 5000 "druggable" genes, predominately enzymes and receptors (34,35). Synthesis of siRNA was performed with standard phosphoramidite chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…The kinase siRNA SMARTpool library (Dharmacon, catalog no. H-003500) and the four siRNAs targeting 5,000 druggable genes (Human Druggable Genome siRNA Set V1.0 [Qiagen]) were transfected into the HCV replicon cells as previously described (21,23,48). The total number of siRNAs screened was 20,779, of which 20,000 were 4 individual siRNAs targeting 5,000 druggable genes and 779 SMARTpool kinases.…”
Section: Methodsmentioning
confidence: 99%
“…Although the specific role of AKT3 in colorectal cancer has not been established, previous studies have suggested AKT3 as a possible mitotic regulator (43,44). Because the inhibition of AURKB causes cytokinetic failure and aneuploidy, and a possible role of AKT in microtubule stabilization has been suggested (45), we suspected that AKT3 may have non-apoptotic activity associated with the cytokinetic machinery, which might counteract aneuploidy induction by AURKis and modulate the chemosensitivity of cancer cells to AURKi.…”
Section: Discussionmentioning
confidence: 94%